Analysis of strategic methodologies in the initial education during the Covid-19 - Maria Fernanda Reyes Santacruz; Margot Mercedes García Espinoza; Ana Maria Uribe Veintimilla (Universidad Ciencia y Tecnología, 2022)
The present work is an exploratory and descriptive study of the methodological strategies implemented by teachers working online in five educational institutions during the COVID-19 pandemic. The study is based on the review of an extensive bibliography and the use of quantitative and qualitative methods.Parents and students answered a survey with in-depth structured questions. Results showed that although parents were unhappy with the teaching methodologies used, teachers were highly motivated and committed to their teaching practice.